2012
DOI: 10.1186/1476-511x-11-175
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids do not pay the toll: effect of SFA and PUFA on human adipose tissue and mature adipocytes inflammation

Abstract: BackgroundOn the basis that high fat diet induces inflammation in adipose tissue, we wanted to test the effect of dietary saturated and polysunsaturated fatty acids on human adipose tissue and adipocytes inflammation. Moreover we wanted to determine if TLR2 and TLR4 are involved in this pathway.MethodsHuman adipose tissue and adipocytes primary cultures were treated with endotoxin-free BSA conjugated with SFA (lauric acid and palmitic acid - LA and PA) and PUFA (eicosapentaeneic acid, docosahexaenoic acid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 52 publications
6
56
0
1
Order By: Relevance
“…Oleic acid down-regulated TNF-α and IL-6 in human adipose tissue and adipocyte cultures [32]. However, in another study, oleic acid had no effect on the TNF-α and IL-10 mRNA expression [17].…”
Section: Discussionmentioning
confidence: 98%
“…Oleic acid down-regulated TNF-α and IL-6 in human adipose tissue and adipocyte cultures [32]. However, in another study, oleic acid had no effect on the TNF-α and IL-10 mRNA expression [17].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the absence of TLR2 was shown to attenuate local inflammatory cytokine expression and enhance insulin action in the liver 54 . Although TLR2 is implicated in the inflammatory response in high-fat diet (HFD)-induced obesity in rodents and in human gene expression studies 55 , saturated and polyunsaturated fatty acids did not elicit proinflammatory effects in human adipose tissue and primary adipocyte culture 56 . Conversely, administration of a HFD for 1 week to healthy males reduced the expression of TLR2 57 .…”
Section: [H3] Tlr2 and Tlr4mentioning
confidence: 99%
“…Moreover, Vandanmagsar et al [100] showed that macrophage inflammation was also mediated by an excess of fatty acids (FAs) via TLR or NOD-like receptor family, one of which is the NOD-like receptor family, the pyrin domain containing 3 (NLRP3) dependent pathway. However, there was one study showing that endotoxin-free, free fatty acids did not have the ability to activate TLR4 and thereby cause inflammation [101]. More importantly, they showed that some polyunsaturated fatty acids exerted an anti-inflammatory action in human adipose tissue and adipocytes.…”
Section: Role Of Hmgb1 In Type 2 Diabetesmentioning
confidence: 99%